De novo isolated myeloid sarcoma: comparative analysis of survival in 19 consecutive cases. (3rd August 2021) - Begna, Kebede H.; Kittur, Jaya; Yui, Jennifer; Gangat, Naseema; Patnaik, Mrinal M.; Al‐Kali, Aref; Elliott, Michelle A.; Hogan, William J.; Litzow, Mark R.; Hook, Christopher C.; Wolanskyj, Alexandra P.; Howard, Matthew T.; et al.
Summary: Institutional database search (1999–2020) for acute myeloid leukaemia (AML) identified 109 cases of myeloid sarcoma (MS), of which 19 were isolated and presented de novo . The latter displayed longer survival (median 78 months), compared to MS with synchronous intramedullary AML ( n  = 32; median 16 months) and de novo AML without MS ( n  = 729; median 22 months; P  = 0·13). However, the difference in survival was no longer apparent after accounting for bone marrow cytogenetic risk status ( P  = 0·67). Treatment‐induced MS tumour resolution was not affected by the presence of intramedullary disease ( P  = 0·61). The current study clarifies the prognosis of de novo isolated MS, in the context of AML.